The optomechanical design of the Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Trilling, D.E.; Hartman, Z.D.; Collins, M.; Von Braun, K.; Gehring, J. (SPIE, 2020)
The Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) is a new speckle imaging instrument available on the 4.3-m Lowell Discovery Telescope (LDT). QWSSI is built to efficiently make use of collected photons and available detector area. The instrument images on a single Electron Multiplying CCD (EMCCD) at four wavelengths in the optical (577, 658, 808, and 880nm) with 40nm bandpasses. Longward of 1μm, two imaging wavelengths in the NIR are collected at 1150 and 1570nm on two InGaAs cameras with 50nm bandpasses. All remaining non-imaging visible light is then sent into a wavefront EMCCD. All cameras are operated synchronously via concurrent triggering from a timing module. With the simultaneous wavefront sensing, QWSSI characterizes atmospheric aberrations in the wavefront for each speckle frame. This results in additional data that can be utilized during post-processing, enabling advanced techniques such as Multi-Frame Blind Deconvolution. The design philosophy was optimized for an inexpensive, rapid build; virtually all parts were commercial-off-the-shelf (COTS), and custom parts were fabricated or 3D printed on-site. QWSSI's unique build and capabilities represent a new frontier in civilian high-resolution speckle imaging. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: 3D printers; Aberrations; Additional datum; Atmospheric aberration; Cameras; Commercial off-the-shelf; Convolution; Design philosophy; Diffraction-limited imaging; Gallium alloys; Gallium compounds; Indium alloys; Instrument design; Interferometers; Interferometry; Light; Multi-frame blind deconvolution; Opto-mechanical design; Optomechanics; Semiconducting indium gallium arsenide; Semiconductor alloys; Speckle; Speckle imaging; Speckle interferometer; Stellar proper- ties; Wave-front sensing; Wavefront-sensing; Wavefronts; dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2020)
Keywords: dept.phy

Toward an imaging capability with the Southern Connecticut Stellar Interferometer - Klaucke, P.M.; Pellegrino, R.A.; Weiss, S.A.; Horch, E.P. (SPIE, 2020)
The Southern Connecticut Stellar Interferometer (SCSI) is an intensity interferometer that is designed to use correlated photon arrival times to determine the geometry of stars. Originally a low-cost, two-telescope instrument that used a 1-pixel single-photon avalanche diode (SPAD) detector at the focal plane of each telescope to record photon events, it is now being upgraded to include a third telescope. This will allow for the simultaneous detection of the photon correlation at three baselines, and thus the ability to map out the two-dimensional geometry of the source much more efficiently than with the two-telescope arrangement. Recent papers in the literature suggest that it may be possible to derive phase information in the Fourier domain from such triple correlations for the brightest stars, potentially giving SCSI an imaging capability. Prior to investigating this possibility, steps must be taken to maximize the observing efficiency of the SCSI. We present here our latest efforts in achieving better pointing, tracking, and collimation with our telescopes, and we discuss our first modeling results of the three-telescope situation in order to understand under what conditions the upgraded SCSI could retrieve imaging information. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Avalanche diodes; Correlation interferometry; Hanbury Brown and Twiss Effect; Image reconstruction; Imaging capabilities; Imaging information; Interferometers; Interferometry; Observing efficiency; Optical intensity interferometry; Particle beams; Phase recovery; Photons; Simultaneous detection; Single photon avalanche diode; Stars; Stellar interferometers; Telescope instruments; Telescopes; Two-dimensional geometry; dept.phy

Visual Orbits of Spectroscopic Binaries with the CHARA Array. III. HD 8374 and HD 24546 - Lester, Kathryn V.; Fekel, Francis C.; Muterspaugh, Matthew; Gies, Douglas R.; Schaefer, Gail H.; Farrington, Christopher D.; Guo, Zhao; Matson, Rachel A.; Monnier, John D.; Brummelaar, Theo ten; Sturmann, Judit; Weiss, Samuel A. (The Astronomical Journal, 2020)
We present the visual orbits of two long-period spectroscopic binary stars, HD 8374 and HD 24546, using interferometric observations acquired with the CHARA Array and the Palomar Testbed Interferometer. We also obtained new radial velocities from echelle spectra using the APO 3.5 m and Fairborn 2.0 m telescopes. By combining the visual and spectroscopic observations, we solve for the full, three-dimensional orbits and determine the stellar masses and distances to within 3% uncertainty. We then estimate the effective temperature and radius of each component star through Doppler tomography and spectral energy distribution analyses, in order to compare the observed stellar parameters to the predictions of stellar evolution models. For HD 8374, we find masses of M 1 = 1.636 ± 0.050M ⊙ and M 2 = 1.587 ± 0.049M ⊙, radii of R 1 = 1.84 ± 0.05R ⊙ and R 2 = 1.66 ± 0.12R ⊙, temperatures of K and K, and an estimated age of 1.0 Gyr. For HD 24546, we find masses of M 1 = 1.434 ± 0.014M ⊙ and M 2 = 1.409 ± 0.014M ⊙, radii of R 1 = 1.67 ± 0.06R ⊙ and R 2 = 1.60 ± 0.10R ⊙, temperatures of K and K, and an estimated age of 1.4 Gyr. HD 24546 is therefore too old to be a member of the Hyades cluster, despite its physical proximity to the group.
Keywords: dept.phy; peer-reviewed

Measurement of the mass difference and the binding energy of the hypertriton and antihypertriton - STAR Collaboration (Nature Physics, 2020)
According to the CPT theorem, which states that the combined operation of charge conjugation, parity transformation and time reversal must be conserved, particles and their antiparticles should have the same mass and lifetime but opposite charge and magnetic moment. Here, we test CPT symmetry in a nucleus containing a strange quark, more specifically in the hypertriton. This hypernucleus is the lightest one yet discovered and consists of a proton, a neutron and a Λ hyperon. With data recorded by the STAR detector1–3 at the Relativistic Heavy Ion Collider, we measure the Λ hyperon binding energy BΛ for the hypertriton, and find that it differs from the widely used value4 and from predictions5–8, where the hypertriton is treated as a weakly bound system. Our results place stringent constraints on the hyperon–nucleon interaction9,10 and have implications for understanding neutron star interiors, where strange matter may be present11. A precise comparison of the masses of the hypertriton and the antihypertriton allows us to test CPT symmetry in a nucleus with strangeness, and we observe no deviation from the expected exact symmetry.
Keywords: Binding energy; Charge conjugation; Colliding beam accelerators; Combined operations; Cpt symmetries; Heavy ions; Magnetic moments; Mass difference; Opposite charge; Relativistic Heavy Ion Collider; Stars; Stringent constraints; Time reversal; dept.phy; peer-reviewed

Human glioma tumors detection by a portable visible resonance Raman analyzer with a hand-held optical fiber probe - Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Zhao, Mingyue; Zheng, Jichun; Zhang, Liang; Zhang, Mingqian; Liang, Qijun; Go, Yun Ii; et al. (Biomedical Vibrational Spectroscopy 2020: Advances in Research and Industry, 2020)
Based on Visible Resonance Raman (VRR) method, we have developed a novel label-free portable VRR LRR2000 Raman analyzer with a portable fiber-optic probe and used it for the classification of human gliomas ex vivo and for the analysis of changes in tumor chemical compositions in molecular level. The purpose of this study was to examine the performance of the LRR2000 Raman analyzer as an optical biopsy tool for detecting human brain tumors compared to the commercial laboratory HR800 and WITec300 micro confocal Raman spectroscopy instruments. As of 2018, a total 1,938 VRR spectra were collected using LRR2000, HR800 and WITec300 Raman system, ex vivo. Identification of the four grades of glioma tumors and control tissues was performed based on the characteristic native molecular fingerprints. LRR2000 demonstrated consistent diagnostic results with HR800 and WITec300 Raman systems. LRR2000 showed the advantages of high speed, convenience and low cost compared to the two confocal micro Raman systems. Using artificial intelligence (AI)-based analysis of part of the data, the cross-validated accuracy for identifying glioma tumors is ~90% compared with gold standard histopathology examination.
Keywords: Biopsy; Brain; Chemical analysis; Handhelds; Histology; Human brain; Industrial research; Molecular biology; Optical biopsies; Optical fibers; Optical molecular Pathology; Palmprint recognition; Principal component analysis; Principle component analysis; Probes; Resonance; Resonance Raman; Spectroscopy; Spectrum analysis; Support vector machines; Tissue engineering; Tumors; Vibrational spectroscopy; dept.phy; glioma tumor; handheld LRR2000 analyzer; human brain tissues; optical biopsy; principle component analysis(PCA); support vector machine (SVM); visible resonance Raman (VRR)

Measurement of inclusive J/ψ polarization in p+p collisions at s =200 GeV by the STAR experiment - STAR Collaboration (Physical Review D, 2020)
We report on new measurements of inclusive J/ψ polarization at midrapidity in p+p collisions at √s=200 GeV by the STAR experiment at the Relativistic Heavy Ion Collider. The polarization parameters, λθ, λϕ, and λθϕ, are measured as a function of transverse momentum (pT) in both the helicity and Collins-Soper (CS) reference frames within pT<10 GeV/c. Except for λθ in the CS frame at the highest measured pT, all three polarization parameters are consistent with 0 in both reference frames without any strong pT dependence. Several model calculations are compared with data, and the one using the Color Glass Condensate effective field theory coupled with nonrelativistic QCD gives the best overall description of the experimental results, even though other models cannot be ruled out due to experimental uncertainties.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of net- Λ fluctuations measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2020)
The measurements of particle multiplicity distributions have generated considerable interest in understanding the fluctuations of conserved quantum numbers in the quantum chromodynamics (QCD) hadronization regime, in particular near a possible critical point and near the chemical freeze-out. Net-protons and net-kaons have been used as proxies for the net-baryon number and net-strangeness, respectively. We report the measurement of efficiency- and centrality-bin width-corrected cumulant ratios (C2/C1, C3/C2) of net-Λ distributions, in the context of both strangeness and baryon number conservation, as a function of collision energy, centrality, and rapidity. The results are for Au+Au collisions at five beam energies (√sNN=19.6, 27, 39, 62.4, and 200 GeV) recorded with the Solenoidal Tracker at RHIC (STAR). We compare our results to the Poisson and negative binomial (NBD) expectations, as well as to ultrarelativistic quantum molecular dynamics (UrQMD) and hadron resonance gas (HRG) model predictions. Both NBD and Poisson baselines agree with data within the statistical and systematic uncertainties. UrQMD describes the measured net-ΛC1 and C3 at 200 GeV reasonably well but deviates from C2, and the deviation increases as a function of collision energy. The ratios of the measured cumulants show no features of critical fluctuations. The chemical freeze-out temperatures extracted from a recent HRG calculation, which was successfully used to describe the net-proton, net-kaon, and net-charge data, indicate Λ freeze-out conditions similar to those of kaons. However, large deviations are found when comparing with temperatures obtained from net-proton fluctuations. The net-Λ cumulants show a weak but finite dependence on the rapidity coverage in the acceptance of the detector, which can be attributed to quantum number conservation.
Keywords: dept.phy; peer-reviewed

Underlying event measurements in p+p collisions at s =200 GeV at RHIC - STAR Collaboration (Physical Review D, 2020)
Particle production sensitive to nonfactorizable and nonperturbative processes that contribute to the underlying event associated with a high transverse momentum (pT) jet in proton+proton collisions at √s=200 GeV is studied with the STAR detector. Each event is divided into three regions based on the azimuthal angle with respect to the highest-pT jet direction: in the leading jet direction (“Toward”), opposite to the leading jet (“Away”), and perpendicular to the leading jet (“Transverse”). In the Transverse region, the average charged particle density is found to be between 0.4 and 0.6 and the mean transverse momentum, ⟨pT⟩, between 0.5 and 0.7 GeV/c for particles with pT>0.2 GeV/c at mid-pseudorapidity (|η|<1) and jet pT>15 GeV/c. Both average particle density and ⟨pT⟩ depend weakly on the leading jet pT. Closer inspection of the Transverse region hints that contributions to the underlying event from initial- and final-state radiation are significantly smaller in these collisions than at the higher energies, up to 13 TeV, recorded at the LHC. Underlying event measurements associated with a high-pT jet will contribute to our understanding of QCD processes at hard and soft scales at RHIC energies, as well as provide constraints to modeling of underlying event dynamics.
Keywords: dept.phy; peer-reviewed

Bulk properties of the system formed in Au+Au collisions at sNN =14.5 GeV at the BNL STAR detector - STAR Collaboration (Physical Review C, 2020)
We report systematic measurements of bulk properties of the system created in Au+Au collisions at √sNN=14.5 GeV recorded by the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum spectra of π±, K±, and p(¯p) are studied at midrapidity (|y|<0.1) for nine centrality intervals. The centrality, transverse momentum (pT), and pseudorapidity (η) dependence of inclusive charged particle elliptic flow (v2), and rapidity-odd charged particles directed flow (v1) results near midrapidity are also presented. These measurements are compared with the published results from Au+Au collisions at other energies, and from Pb+Pb collisions at √sNN=2.76 TeV. The results at √sNN=14.5 GeV show similar behavior as established at other energies and fit well in the energy dependence trend. These results are important as the 14.5-GeV energy fills the gap in μB, which is of the order of 100 MeV, between √sNN=11.5 and 19.6 GeV. Comparisons of the data with UrQMD and AMPT models show poor agreement in general.
Keywords: dept.phy; peer-reviewed

Measurement of groomed jet substructure observables in p+p collisions at s=200 GeV with STAR - STAR Collaboration (Physics Letters B, 2020)
In this letter, measurements of the shared momentum fraction (zg) and the groomed jet radius (Rg), as defined in the SoftDrop algorithm, are reported in p+p collisions at s=200 GeV collected by the STAR experiment. These substructure observables are differentially measured for jets of varying resolution parameters from R=0.2−0.6 in the transverse momentum range 15<pT,jet<60 GeV/c. These studies show that, in the pT,jet range accessible at s=200 GeV and with increasing jet resolution parameter and jet transverse momentum, the zg distribution asymptotically converges to the DGLAP splitting kernel for a quark radiating a gluon. The groomed jet radius measurements reflect a momentum-dependent narrowing of the jet structure for jets of a given resolution parameter, i.e., the larger the pT,jet, the narrower the first splitting. For the first time, these fully corrected measurements are compared to Monte Carlo generators with leading order QCD matrix elements and leading log in the parton shower, and to state-of-the-art theoretical calculations at next-to-leading-log accuracy. We observe that PYTHIA 6 with parameters tuned to reproduce RHIC measurements is able to quantitatively describe data, whereas PYTHIA 8 and HERWIG 7, tuned to reproduce LHC data, are unable to provide a simultaneous description of both zg and Rg, resulting in opportunities for fine parameter tuning of these models for p+p collisions at RHIC energies. We also find that the theoretical calculations without non-perturbative corrections are able to qualitatively describe the trend in data for jets of large resolution parameters at high pT,jet, but fail at small jet resolution parameters and low jet transverse momenta.
Keywords: Groomed jet radius; Jet substructure; SoftDrop; Splitting function; dept.phy; peer-reviewed

Investigation of the linear and mode-coupled flow harmonics in Au+Au collisions at sNN = 200 GeV - STAR Collaboration (Physics Letters B, 2020)
Flow harmonics (vn) of the Fourier expansion for the azimuthal distributions of hadrons are commonly employed to quantify the azimuthal anisotropy of particle production relative to the collision symmetry planes. While lower order Fourier coefficients (v2 and v3) are more directly related to the corresponding eccentricities of the initial state, the higher-order flow harmonics (vn>3) can be induced by a mode-coupled response to the lower-order anisotropies, in addition to a linear response to the same-order anisotropies. These higher-order flow harmonics and their linear and mode-coupled contributions can be used to more precisely constrain the initial conditions and the transport properties of the medium in theoretical models. The multiparticle azimuthal cumulant method is used to measure the linear and mode-coupled contributions in the higher-order anisotropic flow, the mode-coupled response coefficients, and the correlations of the event plane angles for charged particles as functions of centrality and transverse momentum in Au+Au collisions at nucleon-nucleon center-of-mass energy sNN= 200 GeV. The results are compared to similar LHC measurements as well as to several viscous hydrodynamic calculations with varying initial conditions.
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Results on total and elastic cross sections in proton–proton collisions at s=200 GeV - STAR Collaboration (Physics Letters B, 2020)
We report results on the total and elastic cross sections in proton-proton collisions at s=200 GeV obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section was measured in the squared four-momentum transfer range 0.045≤−t≤0.135 GeV2. The value of the exponential slope parameter B of the elastic differential cross section dσ/dt∼e−Bt in the measured −t range was found to be B=14.32±0.09(stat.)−0.28+0.13(syst.) GeV−2. The total cross section σtot, obtained from extrapolation of the dσ/dt to the optical point at −t=0, is σtot=54.67±0.21(stat.)−1.38+1.28(syst.) mb. We also present the values of the elastic cross section σel=10.85±0.03(stat.)−0.41+0.49(syst.) mb, the elastic cross section integrated within the STAR t-range σeldet=4.05±0.01(stat.)−0.17+0.18(syst.) mb, and the inelastic cross section σinel=43.82±0.21(stat.)−1.44+1.37(syst.) mb. The results are compared with the world data.
Keywords: Diffraction; Elastic scattering; Proton-proton collisions; dept.phy; peer-reviewed

Glioma tumors classified using visible resonance raman spectroscopy and machine learning - Wu, Binlin; Zhou, Yan; Zhang, Liang; Zhang, Shengjia; Yu, Xinguang; Wang, Eric; Zhu, Ke; Liu, Cheng-hui; Alfano, Robert R. (The Optical Society, 2020)
Machine learning algorithms were used to classify and analyze spectral data collected by visible resonance Raman spectroscopy to distinguish normal human brain tissue and glioma tumor tissues at different grades and show promising results. © OSA 2020 © 2020 The Author(s)
Keywords: dept.phy; ⛔ No DOI found

Measurement of away-side broadening with self-subtraction of flow in Au+Au collisions at √sNN = 200 GeV - STAR Collaboration (Chinese Physics C, 2020)
High transverse momentum ( ) particle production is suppressed owing to the parton (jet) energy loss in the hot dense medium created in relativistic heavy-ion collisions. Redistribution of energy at low-to-modest has been difficult to measure, owing to large anisotropic backgrounds. We report a data-driven method for background evaluation and subtraction, exploiting the away-side pseudorapidity gaps, to measure the jetlike correlation shape in Au+Au collisions at GeV in the STAR experiment. The correlation shapes, for trigger particles and various associated particle ranges within , are consistent with Gaussians, and their widths increase with centrality. The results indicate jet broadening in the medium created in central heavy-ion collisions.
Keywords: dept.phy; di-hadron correlations; heavy-ion; jet; peer-reviewed

Measurement of the central exclusive production of charged particle pairs in proton-proton collisions at √s = 200 GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2020)
We report on the measurement of the Central Exclusive Production of charged particle pairs h+h− (h = π, K, p) with the STAR detector at RHIC in proton-proton collisions at s$$ \sqrt{s} $$= 200 GeV. The charged particle pairs produced in the reaction pp → p′ + h+h− + p′ are reconstructed from the tracks in the central detector and identified using the specific energy loss and the time of flight method, while the forward-scattered protons are measured in the Roman Pot system. Exclusivity of the event is guaranteed by requiring the transverse momentum balance of all four final-state particles. Differential cross sections are measured as functions of observables related to the central hadronic final state and to the forward-scattered protons. They are measured in a fiducial region corresponding to the acceptance of the STAR detector and determined by the central particles’ transverse momenta and pseudorapidities as well as by the forward-scattered protons’ momenta. This fiducial region roughly corresponds to the square of the four-momentum transfers at the proton vertices in the range 0.04 GeV2 < −t1, −t2 < 0.2 GeV2, invariant masses of the charged particle pairs up to a few GeV and pseudorapidities of the centrally-produced hadrons in the range |η| < 0.7. The measured cross sections are compared to phenomenological predictions based on the Double Pomeron Exchange (DPE) model. Structures observed in the mass spectra of π+π− and K+K− pairs are consistent with the DPE model, while angular distributions of pions suggest a dominant spin-0 contribution to π+π− production. For π+π− production, the fiducial cross section is extrapolated to the Lorentz-invariant region, which allows decomposition of the invariant mass spectrum into continuum and resonant contributions. The extrapolated cross section is well described by the continuum production and at least three resonances, the f0(980), f2(1270) and f0(1500), with a possible small contribution from the f0(1370). Fits to the extrapolated differential cross section as a function of t1 and t2 enable extraction of the exponential slope parameters in several bins of the invariant mass of π+π− pairs. These parameters are sensitive to the size of the interaction region.
Keywords: Diffraction; Forward physics; Hadron-Hadron scattering (experiments); dept.phy; peer-reviewed

Measurement of D0 -meson + hadron two-dimensional angular correlations in Au+ Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2020)
Open heavy-flavor hadrons provide unique probes of the medium produced in ultrarelativistic heavy-ion collisions. Due to their increased mass relative to light-flavor hadrons, long lifetime, and early production in hard-scattering interactions, they provide access to the full evolution of the partonic medium formed in heavy-ion collisions. This paper reports two-dimensional (2D) angular correlations between neutral D mesons and unidentified charged particles produced in minimum-bias Au+Au collisions at √sNN=200GeV. D0 and ¯¯¯D0 mesons are reconstructed via their weak decay to K∓π± using the Heavy Flavor Tracker in the Solenoidal Tracker at RHIC experiment. Correlations on relative pseudorapidity and azimuth (Δη,Δϕ) are presented for peripheral, midcentral, and central collisions with D0 transverse momentum from 2–10GeV/c. Attention is focused on the 2D peaked correlation structure near the triggered D0 meson, the near-side (NS) peak, which serves as a proxy for a charm-quark-containing jet. The correlated NS yield of charged particles per D0 meson and the 2D widths of the NS peak increase significantly from peripheral to central collisions. These results are compared with similar correlations using unidentified charged particles, consisting primarily of light-flavor hadrons, at similar trigger particle momenta. Similar per-trigger yields and widths of the NS correlation peak are observed. The present results provide additional evidence that D0 mesons undergo significant interactions with the medium formed in heavy-ion collision and show, for the first time, significant centrality evolution of the NS 2D peak in the correlations of particles associated with a heavy-flavor hadron produced in these collisions.
Keywords: dept.phy; peer-reviewed

First measurement of λc baryon production in au+au collisions at sNN=200 GeV - STAR Collaboration (Physical Review Letters, 2020)
We report on the first measurement of the charmed baryon Λ±c production at midrapidity (|y|<1) in Au+Au collisions at √sNN=200 GeV collected by the STAR experiment at the Relativistic Heavy Ion Collider. The Λc/D0 [denoting (Λ+c+Λ−c)/(D0+¯D0)] yield ratio is measured to be 1.08±0.16 (stat)±0.26 (sys) in the 0%–20% most central Au+Au collisions for the transverse momentum (pT) range 3<pT<6 GeV/c. This is significantly larger than the pythia model calculations for p+p collisions. The measured Λc/D0 ratio, as a function of pT and collision centrality, is comparable to the baryon-to-meson ratios for light and strange hadrons in Au+Au collisions. Model calculations including coalescence hadronization for charmed baryon and meson formation reproduce the features of our measured Λc/D0 ratio.
Keywords: Au+Au collisions; Bosons; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronization; Hadrons; Heavy ions; Mid-rapidity; Model calculations; Particle detectors; Relativistic Heavy Ion Collider; STAR experiment; Transverse momenta; Yield ratios; dept.phy; peer-reviewed

Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

A hot terrestrial planet orbiting the bright M dwarf L 168-9 unveiled by TESS - Astudillo-Defru, N.; Cloutier, R.; Wang, S. X.; Teske, J.; Brahm, R.; Hellier, C.; Ricker, G.; Vand erspek, R.; Latham, D.; Seager, S.; Winn, J. N.; Jenkins, J. M.; et al. (Astronomy & Astrophysics, 2020)
We report the detection of a transiting super-Earth-sized planet (R = 1.39 ± 0.09 R⊕ ) in a 1.4-day orbit around L 168-9 (TOI-134), a bright M1V dwarf (V = 11, K = 7.1) located at 25.15 ± 0.02 pc. The host star was observed in the first sector of the Transiting Exoplanet Survey Satellite (TESS) mission. For confirmation and planet mass measurement purposes, this was followed up with ground-based photometry, seeing-limited and high-resolution imaging, and precise radial velocity (PRV) observations using the HARPS and Magellan/PFS spectrographs. By combining the TESS data and PRV observations, we find the mass of L 168-9 b to be 4.60 ± 0.56 M⊕ and thus the bulk density to be 1.74-0.33+0.44 times higher than that of the Earth. The orbital eccentricity is smaller than 0.21 (95% confidence). This planet is a level one candidate for the TESS mission's scientific objective of measuring the masses of 50 small planets, and it is one of the most observationally accessible terrestrial planets for future atmospheric characterization. © ESO 2020.
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Solar and Stellar Astrophysics; Atmospheric characterization; Earth (planet); High-resolution imaging; Mass measurements; Orbital eccentricity; Orbits; Planetary systems; Planets; Radial velocity; Scientific objectives; Seeing limited; Stars: individual: L 168-9; Stars: late-type; Techniques: photometric; Techniques: radial velocities; Terrestrial planets; dept.phy; peer-reviewed; planetary systems; stars: individual: L 168-9; stars: late-type; techniques: photometric; techniques: radial velocities

Distinguishing metastatic triple-negative breast cancer from nonmetastatic breast cancer using second harmonic generation imaging and resonance Raman spectroscopy - Bendau, Ethan; Smith, Jason; Zhang, Lin; Ackerstaff, Ellen; Kruchevsky, Natalia; Wu, Binlin; Koutcher, Jason A.; Alfano, Robert; Shi, Lingyan (Journal of Biophotonics, 2020)
Triple-negative breast cancer (TNBC) is an aggressive subset of breast cancer that is more common in African-American and Hispanic women. Early detection followed by intensive treatment is critical to improving poor survival rates. The current standard to diagnose TNBC from histopathology of biopsy samples is invasive and time-consuming. Imaging methods such as mammography and magnetic resonance (MR) imaging, while covering the entire breast, lack the spatial resolution and specificity to capture the molecular features that identify TNBC. Two nonlinear optical modalities of second harmonic generation (SHG) imaging of collagen, and resonance Raman spectroscopy (RRS) potentially offer novel rapid, label-free detection of molecular and morphological features that characterize cancerous breast tissue at subcellular resolution. In this study, we first applied MR methods to measure the whole-tumor characteristics of metastatic TNBC (4T1) and nonmetastatic estrogen receptor positive breast cancer (67NR) models, including tumor lactate concentration and vascularity. Subsequently, we employed for the first time in vivo SHG imaging of collagen and ex vivo RRS of biomolecules to detect different microenvironmental features of these two tumor models. We achieved high sensitivity and accuracy for discrimination between these two cancer types by quantitative morphometric analysis and nonnegative matrix factorization along with support vector machine. Our study proposes a new method to combine SHG and RRS together as a promising novel photonic and optical method for early detection of TNBC.
Keywords: Breast; Breast Neoplasms; Collagen; Diseases; Factorization; Feature extraction; Female; Harmonic generation; Humans; Label-free detection; Lactate concentration; Magnetic resonance; Mammography; Matrix algebra; Molecular imaging; Morphological features; Morphometric analysis; Nonlinear optics; Nonnegative matrix factorization; Raman spectrometry; Raman spectroscopy; Resonance Raman spectroscopy; Second Harmonic Generation Microscopy; Spectrum Analysis, Raman; Subcellular resolution; Support vector machines; Triple Negative Breast Neoplasms; Triple-negative breast cancers; Tumors; breast; breast tumor; dept.phy; diagnostic imaging; female; human; mammography; peer-reviewed; second harmonic generation microscopy; triple negative breast cancer

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Local RR Lyrae stars: native and alien - Zinn, R; Chen, X; Layden, A C; Casetti-Dinescu, D I (Monthly Notices of the Royal Astronomical Society, 2020)
Measurements of [Fe/H] and radial velocity are presented for 89 RR Lyrae (RRL) candidates within 6 kpc of the Sun. After the removal of two suspected non-RRLs, these stars were added to an existing data base, which yielded 464 RRLs with [Fe/H] on a homogeneous scale. Using data from the Gaia satellite (Data Release 2), we calculated the positions and space velocities for this sample. These data confirm the existence of a thin disc of RRL with [α/Fe] ∼ solar. The majority of the halo RRLs with large total energies have near-zero angular momenta about the Z-axis. Kinematically, these stars closely resemble the Gaia-Sausage/Gaia-Enceladus stars that others have proposed are debris from the merger of a large galaxy with the Milky Way. The metallicity and period distributions of the RRLs and their positions in the period-amplitude diagram suggest that this disrupted galaxy was as massive as the Large Magellanic Cloud and possibly greater. © 2019 The Author(s)
Keywords: Dynamics; Galaxy: formation; Galaxy: kinematics; Stars: variables: RR Lyrae; dept.phy; peer-reviewed